Late Neuroborreliosis in an Erasmus Programme Student - Santos, Fábio Videira (2018)
Lyme disease is an endemic zoonosis, the most prevalent tick-transmitted infection in temperate areas of Europe, North America and Asia. It is a multisystemic disease with cutaneous, musculoskeletal, neurologic and cardiac manifestations, according to the stage of the disease. We describe a case of late neuroborreliosis in an Erasmus programme student living in Porto. We discuss the importance of the epidemiological suspicion, the clinical approach, the diagnostic criteria and the most adequate treatment.